Pengaruh Job Crafting Tehadap Kinerja Pegawai Asn Di Lingkungan Dinas Pendidikan Kota Bandung - Asep Supriatna; Dina Lesmana; Yuyun Mulyati (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
The purpose of this study was to find out and analyze the effect of Job Crafting on ASN Employee Performance in the Bandung City Education Office. Every organization or agency in implementing the program is always directed to achieve its goals. One of the factors that become criteria for achieving the smooth goals of an organization or agency is to measure its performance. Employee performance must be considered because it is one of the keys to success. An agency does not only have ASN employees but also PPPK employees. The State Civil Apparatus is an element of the state apparatus whose duty is to provide services to the public in a professional, honest, fair and equitable manner in carrying out state, government and development tasks. This research uses quantitative methods. Data collection techniques were obtained from primary data, namely data obtained from the results of filling out questionnaires. The sample used was all ASN employees in the Bandung City Education Office as many as 198 people. The sample is determined by saturated sampling, namely the entire population is used as a sample. The results of the study show that job crafting has a significant effect on the performance of ASN employees in the Bandung City Education Office.